STUDENTS' PERCEPTION ON THE USE OF CAKE APPLICATION TO IMPROVE SPEAKING SKILL - Haris Hamdani Hamdani; Ferawaty Puspitorini (JALL (Journal of Applied Linguistics and Literacy), 2022)
The purpose of this study was to find out the students’ perception on the use of Cake application to improve speaking skill. The subjects of this research were 12 industrial engineering students of Universitas Bhayangkara Jakarta Raya in the fifth semester. The researchers applied the descriptive qualitative method on this research. The data were gathered through questionnaire and interview. Based on the result of the study, most students agreed that Cake application gave them more chances to improve their speaking skill, they were interested in improving speaking skill independently through Cake application, they were able to practice speaking using Cake application as many times as they wanted, they enjoyed choosing materials on Cake application in improving speaking skill, Using Cake application independently enhanced the confidence to practice speaking skill, using Cake application enabled them to control their own learning, using Cake application in their own time made English language learning more interesting, Cake application could help them solve their problem in improving speaking skill, the practice in Cake application gave them more motivation in improving speaking skill, Cake application was easy to use in improving speaking skill. Four selected students were interviewed about the use of Cake application to improve speaking skill, most of them knew some features of Cake application and understood how to utilize the application. Finally, they would recommend the application to the other students for improving speaking skill.Keywords: perception, cake application, speaking skill